Gender differences in parental educational styles in athletes: Competition level and sport success - González-García, Higinio; Martínez Martínez, Francisco Daniel; Pelegrín Muñoz, Antonia (International Journal of Sports Science&Coaching, 2022)
The goal of this research was to know whether there are differences in parental educational styles depending on gender in athletes and parents, the level of sports success (local successes, national successes and international successes) and the competition level (local competition, national competition and international competition). The sample was made up of 357 Spanish athletes. An ad hoc sociodemographic questionnaire, the Multifactor Self-Assessment Test of Child Adjustment (TAMAI) and the Oviedo Scale of Infrequency of Response (INF-OV), were used to measure the different variables. Results showed that women athletes perceived more protective fathers and men perceived more authoritarian mothers. MANOVA analyses revealed that no gender differences were found depending on the competition level and the level of success. In conclusion, fathers should be aware that they unconsciously can be more protective with girls, otherwise, mothers can be more authoritarian with boys. Thus, these results should be considered by practitioners to create programs to intervene with parents depending on athlete's gender differences.
Keywords: authoritarian; democratic; father; mother; permissive; protective; JCR; Scopus